Assessing the Shared Automated Vehicle´s fleet size using flow optimization in an interurban demand project - Santos, G (2019)
Shared automated vehicles (SAV) are expected to become part of mobility on demand systems in the near future. This research assesses the fleet size of a SAV interurban system. A MIP model was developed to optimize vehicle movements considering flows of vehicles in a time-space network. The consideration of vehicle flows decreases the computational time and allows solving wider problems when compared to routing, which discretizes vehicle movements’ individually. The vehicle fleet size is analyzed having in account different vehicle capacities, different levels of served demand, and respective costs. The model is applied to an interurban transport network connecting municipalities inside the Coimbra district, Portugal.